The South Asian Development Paradox : Can Social Outcomes Keep Pace with Growth? - Ghani, Ejaz (World Bank, Washington, DC, 2012)
South Asia has one of the fastest growing economies in the world, yet it is also home to the largest concentration of people living in debilitating poverty. How do the two coexist? The paradox of South Asia is that growth has been instrument in the reducing poverty rates, but poverty rates have not fallen fast enough to reduce the total number of poor people, and their remain huge room for improvement in education, health, and women's economic participation.